2015
DOI: 10.1177/0962280214567141
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy of novel risk factors and markers: A simulation study of the sensitivity of different performance measures for the Cox proportional hazards regression model

Abstract: Predicting outcomes that occur over time is important in clinical, population health, and health services research. We compared changes in different measures of performance when a novel risk factor or marker was added to an existing Cox proportional hazards regression model. We performed Monte Carlo simulations for common measures of performance: concordance indices (c, including various extensions to survival outcomes), Royston’s D index, R2-type measures, and Chambless’ adaptation of the integrated discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…Third, the limited discriminatory ability of the SMART‐REACH model is comparable to previous risk scores for patients with clinically manifest vascular disease 4, 5, 29, 30. Previous studies have shown that additional risk factors are unlikely to result in relevant improvement 4, 38. This discriminatory ability may be due to the fact that selecting patients on the basis of a certain disease (vascular disease) results in a relatively homogenous population, in which discrimination becomes more difficult.…”
Section: Discussionmentioning
confidence: 76%
“…Third, the limited discriminatory ability of the SMART‐REACH model is comparable to previous risk scores for patients with clinically manifest vascular disease 4, 5, 29, 30. Previous studies have shown that additional risk factors are unlikely to result in relevant improvement 4, 38. This discriminatory ability may be due to the fact that selecting patients on the basis of a certain disease (vascular disease) results in a relatively homogenous population, in which discrimination becomes more difficult.…”
Section: Discussionmentioning
confidence: 76%
“…A large number of competing approaches appears possible since there is a large body of literature on goodness-of-fit procedures and a large body on predictive measures. Combinations of these could provide tools analogous to those described here and this has already been considered by some authors (Emura and Chen, 2014;Austin, Pencina, and Steyerberg, 2015). However, in order to make analogous claims to ours concerning predictive performance for some particular combination, we would require equivalent theorems to those presented in Sections 2 and 3.…”
Section: Discussionmentioning
confidence: 78%
“…Harrel's c-index is one of the most popular measures and could be used, as could most of the others, in place of what we propose in this article. In a recent contribution, Austin, Pencina, and Steyerberg (2015) look closely at several of these and, in particular, one of the early suggestions of Kent and O'Quigley (1988). Although not formally proved, O'Quigley, Xu, and Stare (2004) outline reasons to suppose that the measures of Kent andO'Quigley (1988), O'Quigley andFlandre (1994), and Xu and O'Quigley (1999) would behave very similarly.…”
Section: Background To Measures Of Predictive Abilitymentioning
confidence: 99%
“…Since estimates of predictive model performance can vary with the covariate distribution of the subjects, 14 these differences can cause misleading estimates of model performance in the target population.…”
Section: Introductionmentioning
confidence: 99%